Facial Fabrication and Characterization of Novel Ag/AgCl Chloride Ion Sensor Based on Gel-Type Electrolyte - Kim, Seil; Park, Gwangryeol; Ahn, Hong-Ju; Yoo, Bung Uk; Song, In-Hyuck; Lee, Kyu-Hwan; Kim, Kwang Ho; Lim, Jae-Hong; Lee, Joo-Yul (Frontiers in Chemistry, 2020)
In this study, a novel chloride ion (Cl−) sensor based on Ag wire coated with an AgCl layer was fabricated using a gel-type internal electrolyte and a diatomite ceramic membrane, which played an important role in preventing electrolyte leakage from the ion-selective electrode. The sensing performance, including reversibility, response, recovery time, low detection limit, and the long-term stability, was systemically investigated in electrolytes with different Cl− contents. The as-fabricated Cl− sensor could detect Cl− from 1 to 500 mM KCl solution with good linearity. The best response and recovery time obtained for the optimized sensor were 0.5 and 0.1 s, respectively, for 10 mM KCl solution. An exposure period of over 60 days was used to evaluate the stability of the Cl− sensor in KCl solution. A relative error of 2% was observed between the initial and final response potentials. Further, a wireless sensing system based on Arduino was also investigated to measure the response potential of Cl− in an electrolyte. The sensor exhibited high reliability with a low standard error of measurement. This type of sensor is crucial for fabricating wireless Cl− sensors for applications in reinforced concrete structures along with favorable performances.